2007
DOI: 10.1108/14637150710763568
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for implementing enterprise portals

Abstract: Purpose -The goal of this paper is to discuss critical success factors (CSF) for implementing enterprise portals by comparing them with CSF for ERP implementations. Design/methodology/approach -In order to identify and rank CSF for portal implementations, the paper followed a multi-method design, following a two-stage approach with the first stage analyzing the state-of-the-art of portal implementation by interviewing portal integrators in Germany and a follow-up stage with a focus on CSF, thereby identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 22 publications
2
85
0
Order By: Relevance
“…Reengineering of the business process is fundamental to match the requirement of the new system (Remus, 2007). Mismatching between the company business processes and new system functionality needs either customization of the system to match the company processes or redesigning the company processes to be in line with the new system.…”
Section: Business Process Reengineeringmentioning
confidence: 99%
“…Reengineering of the business process is fundamental to match the requirement of the new system (Remus, 2007). Mismatching between the company business processes and new system functionality needs either customization of the system to match the company processes or redesigning the company processes to be in line with the new system.…”
Section: Business Process Reengineeringmentioning
confidence: 99%
“…Thus, tactical CSFs relate instead to short-term aspects and goals of the system implementation project itself, whereas strategic factors aim at the long-term impacts of activities with strong connections to the development of the organization in relation to the mission, vision and core competencies of the business activity. Considering the technological and organizational character of the CSFs, the specificity and significance of technological factors are strongly dependent on the SCM systems themselves, whereas organizational factors focus on corporate culture and its environment with its specific processes and structures [18], [23], [24]. Table 6 gives an overview of the categorization of the top twelve of the identified CSFs in our study with a focus on their ranking.…”
Section: Results Of the Interviewsmentioning
confidence: 99%
“…We oriented around the classification and categorization of the factors according to [23], [24]. The factors of the top three are highlighted.…”
Section: Results Of the Interviewsmentioning
confidence: 99%
“…The finding is not in consistence with results of previous studies. Researchers such as David et al (2015); Sharon et al (2014);Ferry de vit (2011);Remus (2007) and Imanipour et al (2012) have found in their studies that to have good understanding of role of leaders in prevailing mental ability and positive results of working (job satisfaction, organizational commitment and job performance) for employees, they should be involved in e-communications in their working process. In fact, through making them be involved in the electronic processes can be in significant correlation with this issue in psychological terms; meaning that satisfaction and commitment of employees to their job would be enhanced, whereby results and outputs of their work would be also empowered.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%